2017
DOI: 10.1007/s00384-017-2847-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment for uncomplicated and mild complicated diverticulitis: outpatient treatment for everyone

Abstract: Outpatient treatment for uncomplicated/mild complicated diverticulitis is feasible and safe. Prognostic factors of failure necessitating closer follow-up were admission/CT time, Ambrosetti score of 4, and free air around the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
2
13
0
3
Order By: Relevance
“…This paper defines ambulatory care as an in-patient hospital stay up to 24 h only, with discharge to continue treatment at home in an out-patient setting either on oral antibiotics or with an outpatient IV service. This is confirmed by a recent paper by Joliat et al [30] who employed a similar outpatient treatment strategy. These authors found that factors including increasing time to admission CT, Ambrosetti score of 4 and free air around the colon were predictive of treatment failure [30].…”
Section: Inpatient Verses Outpatientsupporting
confidence: 78%
See 1 more Smart Citation
“…This paper defines ambulatory care as an in-patient hospital stay up to 24 h only, with discharge to continue treatment at home in an out-patient setting either on oral antibiotics or with an outpatient IV service. This is confirmed by a recent paper by Joliat et al [30] who employed a similar outpatient treatment strategy. These authors found that factors including increasing time to admission CT, Ambrosetti score of 4 and free air around the colon were predictive of treatment failure [30].…”
Section: Inpatient Verses Outpatientsupporting
confidence: 78%
“…This is confirmed by a recent paper by Joliat et al [30] who employed a similar outpatient treatment strategy. These authors found that factors including increasing time to admission CT, Ambrosetti score of 4 and free air around the colon were predictive of treatment failure [30]. Assuming equivalent patient outcomes, it follows that outpatient treatment can lead to significant savings on health care costs: An Italian group quantified the economic burden of diverticulitis as EUR 3,826 per patient per year, of which, EUR 3,653 for hospital fees, might be avoided.…”
Section: Inpatient Verses Outpatientsupporting
confidence: 78%
“…Most studies selected patients as outpatient treatment candidates based on patient characteristics (such as absence of comorbidities or immunosuppressed state), clinical condition (such as having uncomplicated diverticulitis and ability to tolerate oral intake) and patients’ social environment (adequate family and social network). Importantly, seven studies [ 22 , 28 , 29 , 31 , 33 35 ] also included patients with diverticular abscesses as candidates for outpatient treatment. Although most studies used outpatient treatment protocols that could be used in almost all hospitals (ambulatory treatment at home with an outpatient clinic visit after 4 to 7 days), 3 studies treated their patients in a ‘hospital at home unit’ or ‘home care unit’ [ 26 , 27 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Treatment failure rates of 3–24% are reported, depending on the definition of treatment failure [712]. Reported risk factors for treatment failure are female gender, free fluid or free air around the colon on CT scan, comorbidity (Ambrosetti score > 3), and an ER admission time between midnight and 6 AM [8, 9]. These studies are however hampered by the fact that all patients received antibiotics, which is now considered a redundant treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated clinical risk factors for treatment failure in patients with UD. In the few studies that are available, all patients received antibiotics [8, 9]. The aim of the current study is to assess the clinical course of UD patients who were initially treated without antibiotics and to identify risk factors for treatment failure in this patient group.…”
Section: Introductionmentioning
confidence: 99%